2018
DOI: 10.1039/c7cy02557b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient aqueous phase reduction of nitroarenes catalyzed by phosphine-decorated polymer immobilized ionic liquid stabilized PdNPs

Abstract: Phosphino-decorated polymer immobilised ionic liquid-stabilised PdNPs are highly efficient catalysts for the aqueous phase hydrogenation and transfer hydrogenation of aromatic nitro compounds in batch and continuous flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 106 publications
0
36
0
Order By: Relevance
“…The reduction of nitroarenes is one of the most used catalytic processes since the aniline and their derivatives represent a large part of the market in the organic chemical industry. This reaction implies the transformation of compounds of pollutant nature into intermediates in the industrial productions of agrochemicals, polymers, pharmaceuticals, dyes, and pigments [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of nitroarenes is one of the most used catalytic processes since the aniline and their derivatives represent a large part of the market in the organic chemical industry. This reaction implies the transformation of compounds of pollutant nature into intermediates in the industrial productions of agrochemicals, polymers, pharmaceuticals, dyes, and pigments [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, aromatica mines can be synthesized through catalytic reduction or hydrogenation of the corresponding nitroarenes. [9] Wang and co-workers fabricated heterogeneous nonnoble metal nickel-molybdenum oxide catalystss upported on ordered mesoporous silica SBA-15t hat exhibited excellent catalytic activity for catalytic hydrogenation of nitroarenes with hydrazineh ydrate as hydrogen donor. To date, supported catalysts such as noble-metal catalysts, non-noble metal catalysts, and metal-free catalysts have been reported for catalytic hydrogenationo fn itroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] For example, Doherty et al reported phosphine-decorated, polymer-immobilized, ionic-liquid-stabilized palladium nanoparticles (NPs) for highly efficient hydrogenation of nitroarenes. [9] Wang and co-workers fabricated heterogeneous nonnoble metal nickel-molybdenum oxide catalystss upported on ordered mesoporous silica SBA-15t hat exhibited excellent catalytic activity for catalytic hydrogenation of nitroarenes with hydrazineh ydrate as hydrogen donor. [10] Li and co-workers reported B/N-codoped graphene-like carbon as an efficient metal-free catalyst for the hydrogenation of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…5b,6,13 Due to the strong interaction between transition metals and phosphine ligands, transition metals supported on phosphine functionalized POPs usually exhibited long-term reusability, excellent leaching resistant ability, and high catalytic activities. 6,13,14 Some of them even outperformed the activities of their homogeneous analogues. 6a,15 However, performing an organic reaction in water over a solid catalyst inevitably suffers from poor mass transfer efficiency of the hydrophobic organic substances, and thus, leading to low catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%